IT Infrastructure Security Optimization Strategies for Today's Organizations - Antoni, Kevin Rizki; Sulistiani, Heni; Nunyai, Reiza Fahlevi (LPPM STIKI Malang, 2024)
Information technology (IT) infrastructure security is one of the top priorities for organizations in the digital age. The rapid adoption of technologies such as cloud computing, the Internet of Things (IoT), and artificial intelligence has presented great opportunities for innovation, but also increased the risk of cyberattacks, data theft, and system vulnerabilities. This research aims to identify and develop IT infrastructure security optimization strategies that can enhance the protection of an organization's digital assets. The approach used includes risk analysis, implementation of a comprehensive security framework, and adoption of advanced defense technologies such as encryption, next-generation firewalls, and artificial intelligence-based threat detection systems. The results show that an integrated, adaptive strategy supported by solid policies can improve system resilience while supporting operational flexibility. Thus, this research provides practical recommendations for organizations to build an IT infrastructure that is secure, resilient, and ready to face future challenges.